2021
DOI: 10.1021/jacs.1c11244
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Applications of Polysubstituted Bicyclo[1.1.0]butanes

Abstract: Bicyclo[1.1.0]butanes (BCBs) are valuable substrates in the "strain release" synthesis of polysubstituted fourmembered ring systems, with applications including bioconjugation agents. The introduction of substituents onto the BCB bridges is challenging due to limitations in current methods for the preparation of this bicyclic scaffold, typically necessitating linear syntheses with limited functional group tolerance and/or substituent scope. Here, we report the synthesis of tri-and tetrasubstituted BCBs via dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…Anderson and co-workers recently advanced a solution to this problem by demonstrating that BCBs can be used in directed ortho metalation (DoM)-type reactions ( Scheme 6C ). 68 This innovative approach uses a BCB with an amide at the bridgehead position to direct the deprotonation to the non-bridgehead methylene. sec -BuLi and TMEDA at temperatures as high as −40 °C were identified as ideal for executing this so-called “bridge-metalation”.…”
Section: Recent Approaches To Bcb Constructionmentioning
confidence: 99%
“…Anderson and co-workers recently advanced a solution to this problem by demonstrating that BCBs can be used in directed ortho metalation (DoM)-type reactions ( Scheme 6C ). 68 This innovative approach uses a BCB with an amide at the bridgehead position to direct the deprotonation to the non-bridgehead methylene. sec -BuLi and TMEDA at temperatures as high as −40 °C were identified as ideal for executing this so-called “bridge-metalation”.…”
Section: Recent Approaches To Bcb Constructionmentioning
confidence: 99%
“…5 Despite this significance, current methods are mainly confined to approach mono-and disubstituted 2-oxa-BCHs, and access to polysubstituted (C1, C2, and C3) 2-oxa-BCHs remains a challenge, considering that the functionalization of the backbone (C2) C−H is often nontrivial and usually requires tedious prefunctionalization steps. 6 The development of novel catalytic strategies for the synthesis of polysubstituted 2-oxa-BCHs would not only enrich the toolkit of synthetic chemists but also greatly enlarge the compound library accessible for drug discovery.…”
mentioning
confidence: 99%
“…Significantly, recent studies showed that, 2-oxabicyclo[2.1.1]­hexanes (2-oxa-BCHs), exhibit higher water solubility, improved metabolic stability, and reduced lipophilicity than the corresponding benzene or BCP analogues - thus, their synthesis has attracted tremendous attention (Scheme a) . Despite this significance, current methods are mainly confined to approach mono- and disubstituted 2-oxa-BCHs, and access to polysubstituted (C1, C2, and C3) 2-oxa-BCHs remains a challenge, considering that the functionalization of the backbone (C2) C–H is often nontrivial and usually requires tedious prefunctionalization steps . The development of novel catalytic strategies for the synthesis of polysubstituted 2-oxa-BCHs would not only enrich the toolkit of synthetic chemists but also greatly enlarge the compound library accessible for drug discovery.…”
mentioning
confidence: 99%
“…Some of these moieties are also found directly in natural products or utilized in medicinal chemistry for the introduction of bioisosteres . More specifically, sulfonyl-substituted BCB and housanes are exceptionally bench-stable and have found widespread applicability in strain-release cycloalkylation with either nucleophiles or radical species as well as in formal cycloaddition, where the resulting sulfonyl group serves as a handle for further derivatization (Scheme a, A ). Moreover, in the case of BCB, their structure can be readily diversified via sulfone-directed C–H functionalization ( B ). ,,, While their superior versatility as strain-release reagents is well established, the general access to 1-sulfonylbicyclo[1.1.0]­butanes and housanes from inexpensive and readily available materials remains a challenge, typically requiring six steps and two purifications from sulfonyl chlorides in the case of BCB (Scheme b). ,,, As part of our research program directed at the elaboration and use of reagents of extreme strain such as cyclopropanones, we discovered that these strain-release reagents could be accessed in a streamlined manner via the formation of 3-sulfonylcyclobutanol intermediates susceptible to transannular ring-closure upon activation ( vide infra ). Herein, we report a general procedure for the preparation of 1-sulfonyl-bicyclo[1.1.0]­butanes in a single pot from readily available methyl sulfones and inexpensive epichlorohydrin (Scheme c).…”
mentioning
confidence: 99%